Characterisation of antioxidant defences in three Antarctic notothenioid species from Terra Nova Bay (Ross Sea). - BENEDETTI, MAURA; REGOLI, Francesco; Marco, Nigro (Chemistry and Ecology, 2010)
Oxidative challenge is an important factor affecting the adaptive strategies of Antarctic fish, but data on antioxidant defences in these organisms remain scarce. In this investigation, individual antioxidants and the total oxyradical scavenging capacity (TOSC) were characterised in three notothenioid species, Trematomus bernacchii, Trematomus hansoni and Trematomus newnesi; seasonal fluctuations were further analysed in T. bernacchii sampled during different periods of the reproductive cycle, ice melting and phytoplanktonic blooms. The overall results revealed only limited differences between the three notothenioids, with greater TOSC values in T. hansoni and T. newnesi. The capacity for decomposing hydrogen peroxide via catalase was not particularly enhanced in these fish, in contrast to the prominent role of the enzyme in Antarctic invertebrates. An alternative antioxidant strategy, based on the efficiency of low molecular mass scavengers was suggested, especially for T. bernacchii which had higher levels of glutathione and glutathione reductase; the diet composition of the investigated species might explain the differences in tissue antioxidants. Oxidative stress responses revealed almost constant values between November and January in T. bernacchii, a quite unusual and unexpected result considering the marked changes occurring in several biological and environmental factors. In this respect, the antioxidant efficiency of T. bernacchii would counteract the naturally elevated environmental prooxidant conditions and the associated potential increase in oxidative challenge, i.e. spawning period, sea-ice melting, phytoplanktonic development and the seasonal increase in cadmium bioavailability at Terra Nova Bay.